2004
DOI: 10.1080/18811248.2004.9715543
|View full text |Cite
|
Sign up to set email alerts
|

Use of Real Options in Nuclear Power Plant Valuation in the Presence of Uncertainty with CO2Emission Credit

Abstract: The purpose of this study is to analyze the value of an investment in power generation assets that do not emit CO 2 , by using a real option model. This study evaluates the effects of future uncertainty on investment decision-making, by focusing on the uncertainty of CO 2 emission credits [yen/t-CO 2 ] in the fairly near future in Japan. Electric utilities are required to keep plans to prepare for various future uncertainties such as the price of CO 2 emission credits. The real option approach can evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…While the new information can never fully complete the picture, it can help to reduce the uncertainty in investment. Real option analysis has been applied to energy generation projects that consider different types of options and uncertainties -these include, flexible investment in nuclear power plants in Japan, hydroelectric plants in Brazil and renewable energy projects in the UK (Abadie and Chamorro, 2014;Caminha-Noronha et al, 2006;Kiriyama and Suzuki, 2004).…”
Section: Energy Infrastructure Risks and Investmentmentioning
confidence: 99%
“…While the new information can never fully complete the picture, it can help to reduce the uncertainty in investment. Real option analysis has been applied to energy generation projects that consider different types of options and uncertainties -these include, flexible investment in nuclear power plants in Japan, hydroelectric plants in Brazil and renewable energy projects in the UK (Abadie and Chamorro, 2014;Caminha-Noronha et al, 2006;Kiriyama and Suzuki, 2004).…”
Section: Energy Infrastructure Risks and Investmentmentioning
confidence: 99%
“…The real options approach here is based on the works of Dixit and Pindyck, see, for example, Dixit and Pindyck (1994). Recent applications of real options theory to decision making in the nuclear power industry have included (1) Epaulard and Gallon (2001), which evaluated the European Pressurized-water Reactor (EPR) as a function of uncertainty in natural gas prices, (2) Takizawa, Omori, Suzuki, and Ono (2001), which examined the influence of uranium price uncertainty on the value of building a light water reactor in Japan, (3) Kiriyama and Suzuki (2004), which compared the value of light water reactors with renewables under uncertainty in the price of CO 2 emission rights in Japan, and (4) Gollier, Proult, Thais, and Walgenwitz (2004), which compared the value of a 1200 MW light-water reactor with four 300 MW modular reactors under electricity price uncertainty.…”
Section: New Nuclear Power Plants?mentioning
confidence: 99%
“…In addition to the uncertainty of fossil fuel energy prices, some recent studies have suggested that the factors regarding carbon market should be considered in the evaluations of the economic value of energy technologies including renewable energy, and have made efforts to reflect this factor. Kiriyama and Suzuki [20] evaluated the economic efficiency of nuclear power generation, although it is not in the area of renewable energy, and considered the uncertainty of CO2 emission rights. Szolgayova et al [21] and Fuss et al [22] used real options modelling to illustrate how market uncertainty pertaining to fluctuations of carbon price and the carbon price cap policy influence on investment decisions, profits and carbon emissions in electricity sector.…”
Section: Introductionmentioning
confidence: 99%